Hosting Capacity Distribution System Yogyakarta with Ant Lion Optimization: A Case Multiobjective - Khomarudin, Riki; Putra, Jimmy Trio; Syahputra, Ramadoni; Chamim, Anna Nur Nazilah (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
Penetration of hosting capacity in radial type power distribution systems aims to increase the voltage profile on the end customer side. The more electricity customers increase, the more electricity user load growth will increase. This results in a voltage drop on the end customer side in the radial distribution system, characterized by a voltage exceeding the minimum standard operating acceptable voltage. This paper aims to provide solutions to cases in radial grid type power systems in solve voltage drops. The addition of hosting capacity for distributed renewable energy generators is one of the goals to increase the capacity of the electricity system. This research uses the Ant Lion Optimization algorithm method to try to find the optimal location and capacity of Distributed Generation in the electric power distribution system. Penetration hosting capacity injects renewable energy generation in the form of solar cells. The simulation results show that the increased voltage profile in the electric power distribution system exceeds the minimum voltage drop standard. So that in reducing power losses in the radial type network.